2007
DOI: 10.1111/j.1399-6576.2007.01379.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for acute renal failure requiring dialysis after surgery for congenital heart disease in children

Abstract: A young age, high RACHS-1 score and CPB were independent risk factors for ARF after surgical procedures for congenital heart disease in children. The risk of ARF decreased during the study period. Children with severe ARF spent a longer time in the ICU, and the mortality in ARF patients was higher than that in non-ARF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
76
2
11

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(97 citation statements)
references
References 16 publications
8
76
2
11
Order By: Relevance
“…The number of patients needed to screen varied between 1.5 and 2.6 when uNGAL was measured within 12 hours of surgery. Because the prevalence of the composite event here is consistent with previous literature (32), it is possible to extrapolate these results to other populations. Additionally, preoperative uNGAL concentrations were predictive of the occurrence of the composite endpoint, consistent with a previous report (12) and suggesting that some of the patients had subclinical preoperative AKI, which may have predisposed them to severe AKI after surgery.…”
Section: Predictive Performance Of Ungal For Dialysis Requirement Andsupporting
confidence: 79%
“…The number of patients needed to screen varied between 1.5 and 2.6 when uNGAL was measured within 12 hours of surgery. Because the prevalence of the composite event here is consistent with previous literature (32), it is possible to extrapolate these results to other populations. Additionally, preoperative uNGAL concentrations were predictive of the occurrence of the composite endpoint, consistent with a previous report (12) and suggesting that some of the patients had subclinical preoperative AKI, which may have predisposed them to severe AKI after surgery.…”
Section: Predictive Performance Of Ungal For Dialysis Requirement Andsupporting
confidence: 79%
“…[1,4,13,14] Several studies have attempted to identify the risk factors of ARF requiring RRT in pediatric patients undergoing congenital cardiac surgery. [2,7,14] In consistent with previous studies, [15][16][17] patients who showed recovery of renal function following PD with associated lower CPB and CC times, RACHS-1 category and inotrope scores, BUN and SCr values before PD and a lower time interval between surgery and PD had lower mortality. Additionally, in the present study, higher MAP and CVP scores before PD, late beginning of PD, lower perioperative urine output, and lower diuresis after PD were significant risk factors for increased mortality.…”
Section: Discussionsupporting
confidence: 78%
“…[12,15,16,19,20] The incidence of ARF, which required PD and mortality rate following congenital cardiac surgery in our study population, were 7.9% and 72.2%, respectively. The development of ARF is often related to the results of CPB with the associated complexity of the operation (RACHS-1 category) in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of postoperative acute renal failure (ARF) and/or dysfunction in children after surgical repair for a CHD has been reported to be as high as 32.8%. 32 Risk factors for pediatric ARF after cardiac surgery include, but are not limited to, young age, repair of complex cardiac lesions, duration of cardiopulmonary bypass, circulatory arrest, and low cardiac output postoperatively. 32 Postoperative renal management by critical care nurses may include the administration of different diuretic medications and/or the use of renal replacement therapies such as hemofiltration or peritoneal dialysis.…”
Section: Descriptionmentioning
confidence: 99%